IMPLEMENTASI PROGRAM PENGEMBANGAN INDUSTRI KECIL MENENGAH (IKM) OLEH DINAS PERINDUSTRIAN KABUPATEN BEKASI - Raydhiani Tasya; Hanny Purnamasari; Rachmat Ramdani (Jurnal Pemerintahan dan Politik, 2022)
Small and medium industries or commonly called IKMs are one of the main pillars for the government to create new jobs and ideas and creativity to produce goods with selling value. SMEs are also an important part of the economy for developing countries including Indonesia. Small and Medium Industry (IKM) is one of the industrial sectors that can be used as a foundation to create an entrepreneurial climate that can absorb labor. Small industry has a strategic position, potential and role in achieving national development goals. The method used in this research is descriptive with a qualitative approach. The data collection techniques that the researchers used were interviews, observation and documentation. Actions in data analysis are data reduction, data presentation, conclusion drawing and verification as well as using Charles O. Jones' theory of policy implementation which includes Organization, Interpretation, and Application. The results of this study can be seen that the implementation of the Small and Medium Industry Development Program (IKM) by the Bekasi Regency Industry Office has been going quite well. However, based on research in the field, there are still problems that need to be addressed in order to increase the development of SMEs in realizing national development goals.Keywords: Development, Economics, Industry